Shariah Compliance and Efficiency of Islamic Financial Derivative Instruments: A Comparative Analysis of the Implementation of Islamic Economic Principles. - CAHYA MILA PRATIWI; ANDI DAFFA ZAKY RAMADHAN; SALMA FAKHRANA RAMADHANI; NAJWA JIHAN PUSPITA; PAMELA ALYA DEWI (Dinamis : Journal of Islamic Management and Bussiness, 2025)
This study explores the application of Islamic economic principles in the use of derivative instruments within the development of Islamic finance in Indonesia. Derivatives play a key role in managing financial risks, yet their utilization must align with sharia principles, which prohibit elements such as gharar (uncertainty), maisir (gambling), and riba (usury). The research identifies several major challenges, including regulatory constraints, low levels of Islamic financial literacy, and insufficient market infrastructure. Using a literature review approach, the study concludes that despite these obstacles, strengthening regulatory frameworks, encouraging product innovation, and improving financial literacy can support the optimal use of sharia-compliant derivatives. Therefore, collaboration among regulators, academics, and industry practitioners is essential to foster the development of derivative instruments that adhere to Islamic principles and contribute to the stability of the Islamic financial system in Indonesia.